Araç Plaka Yerinin Saptanması - Beratoğlu, Muhammet S. (Fen Bilimleri Enstitüsü, 2015)
Bu çalışmada, araç plaka tanımanın en önemli adımlarından biri olan plaka yer saptama adımı için ayrıt saptamaya dayalı yeni bir yöntem geliştirilmiştir. İlk olarak Canny ayrıt saptayıcısı kullanılarak görüntünün yatay yönde gradyanları bulunmuştur. Bulunan gradyanlar negatif-pozitif çiftler halinde eşleştirilmiş, tek kalanlar elenmiştir. Ayrıt çiftlerinin arasında kalan benekler morfolojik işlemlerle doldurularak görüntü eşiklenmiştir. Bu görüntü üzerinde bağlı bölgeler analizi yapılarak, plaka karakter adayı öbekleri ayrık olarak elde edilmiştir. Öbeklerin sayıları ve birbirlerine göre konumları uygun olanlar birleştirilmiş ve plaka bölgesi bulunmuştur. Elde edilen bölgeler plaka arka plan renk bilgisi kullanılarak iyileştirilmiştir. Yöntem İTÜ Çoğul Ortam Merkezi-Araç Plaka Tanıma Sistemi (ÇOM-APTS) ile karşılaştırılmıştır. Farklı veritabanları üzerinde yapılan testlere göre geliştirilen yöntem, yer saptamada ortalama %8 daha başarılı olmuştur. Geliştirilen yer saptama yöntemi ÇOM-APTS ile tümleştirilmiştir. Test sonuçlarına göre tümleştirilen sistemin plaka tanıma başarımı yaklaşık %5 artarak %85 düzeyine ulaşmıştır.

This study presents a new edge based license plate localization method for vehicle license plate recognition systems. Firstly, the horizontal gradients of the vehicle image are found by using Canny edge detector. Next, the gradients are matched as negative-positive pairs and the singles are eliminated. Then, by using morphological operators, the pixels between the edge pairs are filled, and as a result a thresholded image that implies the plate character candidates is reached. Connected component analysis is applied to that thresholded image and plate character candidate blobs are separately obtained. After that, plate character candidates are merged to create plate candidates. At the last stage of the method, using plate background color information, plate regions are enhanced. A performance evaluation method is defined for each step of the vehicle plate recognition system, and the proposed method is compared with license plate recognition system (LPRS) which was developed in ITU Multimedia Center. Results of the license plate localization rate for different vehicle image databases are shown that, the proposed method increases the success rate at by 6%. After integrating the new method with the LPRS of ITU Multimedia Center; license plate recognition rate is over performed nearly 5% and is raised to the level of 85% average.
Vehicle License Plate Localization
Tez (Yüksek Lisans) -- İstanbul Teknik Üniversitesi, Fen Bilimleri Enstitüsü, 2003
Thesis (M.Sc.) -- İstanbul Technical University, Institute of Science and Technology, 2003
Keywords: Araç Plaka Tanıma; Plaka Yer Saptama; Ayrıt Saptama; Eşikleme.; Vehicle License Plate Recognition; License Plate Localization; Edge Detection; Thresholding.